2010
DOI: 10.1007/s10668-010-9269-1
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater market and its implications on water resources and agriculture in the southern peri-urban interface, Chennai, India

Abstract: This paper describes the informal groundwater market existing in the urbanperi-urban interface of Chennai. The private water tanker suppliers and packaged water industries utilize the land and water resources of the peri-urban villages. Thus, the groundwater sources in peri-urban areas play a significant role in meeting the growing urban demand. The villages that are experiencing the groundwater market are highly influenced by the urbanization and its related activities, due to their proximity to the city. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…The studies conducted by several researchers were reported the similar evidences in the decline of agriculture and the related implications particularly in the peri-urban contexts (Keith et. al, 2003;Shanmugam et. al, 2010).…”
Section: Status Of Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…The studies conducted by several researchers were reported the similar evidences in the decline of agriculture and the related implications particularly in the peri-urban contexts (Keith et. al, 2003;Shanmugam et. al, 2010).…”
Section: Status Of Agriculturementioning
confidence: 99%
“…The increased labour cost, fertilizer cost, the profitable business of the sale of water for non-agricultural uses, and adequate non-agricultural employment opportunities, decrease the dependency on agricultural activities in the village (Shanmugam et al 2010). Furthermore, the agricultural lands are used for residential purposes due to the increased land value in the peri-urban village (as the lands are highly demanded for non agricultural purposes), which is located very close to the urban centres.…”
Section: Status Of Agriculturementioning
confidence: 99%
“…For well off farmers, water vending is a chance to increase their income, while it deprives poor farmers who cannot afford borewells from their livelihood base. Water vending generally requires less labour input and offers higher profits [20,22,103]. Yet, this new livelihood results in further transformations, as farmers drop out of agriculture and professionalise in water vending [20,22].…”
Section: Emerging and Diversification Water-based Livelihoodsmentioning
confidence: 99%
“…Together with overextraction and pollution, changes in managing the resource, result in changing access to water, with the patterns being determined inter alia by location, socio-economic status, gender, and social identity [18,[20][21][22][23][24]. In many cases, the shortfall of governance is the root cause for these problems.…”
Section: Introductionmentioning
confidence: 99%
“…The suitability of groundwater for various uses majorly depends on quality of groundwater. Hence protecting the quality of groundwater is a major concern (Packialakshmi et al,2011). Water quality index is one of the most efficient tools to converse information on the quality of water to the concerned people and understand the spatial and temporal variation of quality.…”
Section: Introductionmentioning
confidence: 99%